Hemophagocytic lymphohistiocytosis as the initial manifestation of Epstein–Barr virus-related T/NK-cell lymphoproliferative disorders in a pediatric patient: a case report and literature review - Ma, Lianwei; Xing, Xue; Liu, Yonge; Jiang, Wei (Frontiers in Pediatrics, 2025)
Epstein–Barr virus-associated T/Natural Killer-cell lymphoproliferative disorders (EBV-T/NK-LPDs) are rare diseases that predominantly affect children and young adults. We report a case of a 12-year-old child who initially presented with EBV-associated hemophagocytic lymphohistiocytosis (HLH) and later progressed to aggressive NK-cell leukemia (ANKL). Both EBV-HLH and ANKL belong to the spectrum of EBV-T/NK-LPDs, which also includes chronic active EBV infection (CAEBV) of T-cell and NK-cell types, systemic EBV-positive T-cell lymphoma of childhood, extranodal NK/T-cell lymphoma (ENKTL), and primary EBV-positive nodal T/NK-cell lymphoma. The patient initially presented with recurrent high fever, pancytopenia, hepatosplenomegaly, hypertriglyceridemia, and hypofibrinogenemia with a significantly elevated EBV-DNA load. Bone marrow examination indicated a few histiocytes and hemophagocytic cells. Subsequent increases in ferritin and soluble CD25 (sCD25) levels were further consistent with the diagnosis of EBV-HLH. No lymphadenopathy or nasal primary lesion was identified. Further BM flow cytometry and BM cell morphology examination indicated abnormal NK-cell infiltration, leading to the exclusion of ENKTL, primary EBV-positive nodal T/NK-cell lymphoma, and systemic EBV-positive T-cell lymphoma of childhood. A diagnosis of ANKL was highly suspected. This case highlights that when EBV infection triggers a series of complex EBV-T/NK-LPDs occurring sequentially or simultaneously, the differential diagnosis and treatment become difficult, which can easily lead to delays in diagnosis and treatment. Developing optimized diagnostic algorithms and evidence-based treatment strategies is essential to improve outcomes of patients.